Decreased mitochondrial‐related gene expression in adipose tissue after acute sprint exercise in humans: A pilot study - Mona Esbjörnsson; Håkan C. Rundqvist; Barbara Norman; Ted Österlund; Eric Rullman; Jens Bülow; Eva Jansson (Physiological Reports, 2024)
Abstract The aim was to examine the acute effects of sprint exercise (SIT) on global gene expression in subcutaneous adipose tissue (AT) in healthy subjects, to enhance understanding of how SIT influences body weight regulation. The hypothesis was that SIT upregulates genes involved in mitochondrial function and fat metabolism. A total of 15 subjects performed three 30‐s all‐out sprints (SIT). Samples were collected from AT, skeletal muscle (SM) and blood (brachial artery and a subcutaneous AT vein) up to 15 min after the last sprint. Results showed that markers of oxidative stress, such as the purines hypoxanthine, xanthine and uric acid, increased markedly by SIT in both the artery and the AT vein. Purines also increased in AT and SM tissue. Differential gene expression analysis indicated a decrease in signaling for mitochondrial‐related pathways, including oxidative phosphorylation, electron transport, ATP synthesis, and heat production by uncoupling proteins, as well as mitochondrial fatty acid beta oxidation. This downregulation of genes related to oxidative metabolism suggests an early‐stage inhibition of the mitochondria, potentially as a protective mechanism against SIT‐induced oxidative stress.